Morphological and Chemical Analysis of the Molecularly-Imprinted Polymer-Based D-Arabinose Sensor on a Modified Electrode with Functionalized Carbon Nanotubes - Sousa, Miguel S. P. (2019)
he sensors modified carbon nanotubes and molecularly imprinted polymers are an excellent choice for the determination of D-arabinose, because they have high selectivity and sensitivity for analysis. This allows the control and optimization of the second generation ethanol production process, given the clear understanding of the chemical changes that occur through the hydrolysis of lignocellulosic biomass. For this reason, the present work presents a chemical study of the functional groups of the chemical species present on the sensor surface by the Fourier transform infrared spectroscopy (FT-IR) technique and a morphological analysis by the scanning electron microscopy (SEM) technique.